Activating Effects of the Bioactive Compounds From Coffee By-Products on FGF21 Signaling Modulate Hepatic Mitochondrial Bioenergetics and Energy Metabolism in vitro - Rebollo-Hernanz, Miguel; Aguilera, Yolanda; Martín-Cabrejas, Maria A.; Gonzalez de Mejia, Elvira (Frontiers in Nutrition, 2022)
Coffee by-products contain bioactive compounds that have been shown to have the capacity to modulate human metabolism. The goal of this study was to investigate the effects of the main bioactive compounds in coffee by-products and two aqueous extracts from the coffee husk and silverskin on the activation of fibroblast growth factor 21 (FGF21) signaling and the subsequent regulation of mitochondrial bioenergetics and lipid and glucose metabolism. HepG2 cells treated with palmitic acid (PA) were used in a non-alcoholic fatty liver disease (NAFLD) cell model. The bioactive compounds from coffee by-products (50 µmol L−1) and the aqueous extracts from the coffee silverskin and coffee husk (100 µg mL−1) increased ERK1/2 phosphorylation and the secretion of FGF21 (1.3 to 1.9-fold). Coffee by-products’ bioactive compounds counteracted inflammation and PA-triggered lipotoxicity. Oxidative stress markers (ROS, mitochondrial superoxide, and NADPH oxidase) and the activity of antioxidant enzymes (superoxide dismutase and catalase) were modulated through the activation of Nrf2 signaling. Mitochondrial bioenergetics were regulated by enhancing respiration and ATP production via PGC-1α, and the expression of oxidative phosphorylation complexes increased. Coffee by-products’ phytochemicals bioactive compounds decreased lipid accumulation (23–41%) and fatty acid synthase activity (32–65%) and triggered carnitine palmitoyltransferase-1 activity (1.3 to 1.7-fold) by activating AMPK and SREBP-1c pathways. The GLUT2 expression and glucose uptake were increased (58–111%), followed by a promoted glucokinase activity (55–122%), while glucose production and phosphoenolpyruvate carboxykinase activity were reduced due to IRS-1/Akt1 regulation. The bioactive compounds from coffee by-products, primarily chlorogenic and protocatechuic acids, could regulate hepatic mitochondrial function and lipid and glucose metabolism by activating FGF21 and related signaling cascades.